2016
DOI: 10.17265/1539-8080/2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Experience in Accreditation and Quality Assurance in HEIs

Abstract: Quality assurance and accreditation in higher education aims to maintain and raise the quality of education and guarantee the improvement of its standards. It enables the institution to get the necessary input, refine the processes, and raise the standards of its output, in order to meet the previously defined goals and the needs of the stakeholders. This paper discusses issues of accreditation and quality assurance (QA) in Jordan's higher education institutions (HEIs), focusing primarily on the need for profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…As revealed in the current study, the lowest mean percent of an accreditation benefits tool dimensions for faculty staff about (63.4%) and for stakeholders about (71.2%) for the dimension that said "improve human and non-human resources". This result is inconsistent with the study conducted by [25,26] who revealed that accreditation helps to maintain and raise the quality of education, guarantee the improvement of its standards, enables the institution to get the necessary input (such as the overall infrastructure especially the physical space, financial, staffing, programs resources, curriculum design and contents), with refine the educational processes (teaching staff, students, programs, teaching methods, labs computers, etc.) and raise the standards of its output to meet the defined goals (such as the employability, graduate abilities, and stakeholders' satisfaction).…”
Section: Concerning Percentage Distributions Of Sociodemographic Datacontrasting
confidence: 60%
“…As revealed in the current study, the lowest mean percent of an accreditation benefits tool dimensions for faculty staff about (63.4%) and for stakeholders about (71.2%) for the dimension that said "improve human and non-human resources". This result is inconsistent with the study conducted by [25,26] who revealed that accreditation helps to maintain and raise the quality of education, guarantee the improvement of its standards, enables the institution to get the necessary input (such as the overall infrastructure especially the physical space, financial, staffing, programs resources, curriculum design and contents), with refine the educational processes (teaching staff, students, programs, teaching methods, labs computers, etc.) and raise the standards of its output to meet the defined goals (such as the employability, graduate abilities, and stakeholders' satisfaction).…”
Section: Concerning Percentage Distributions Of Sociodemographic Datacontrasting
confidence: 60%
“…Quality assurance and Accreditation in HEIs is considered as one of the major processes in the development of higher education which is connected to the components of the educational process such as (students, teaching staff, programs, teaching methods, facilities and equipment, etc.) [18]. Accreditation is defined as "a process whereby officially appointed external regulatory www.ijacsa.thesai.org bodies, accountable at government level, evaluate educational institutions sing established criteria, standards and procedures" [19].…”
Section: B Quality and Academic Accreditation In Heis In Saudi Arabiamentioning
confidence: 99%